Multidisciplinary and Multisociety Practice Guideline on Reprocessing Flexible Gastrointestinal Endoscopes and Endoscopic Accessories - Cheung, Dae Young; Jang, Byung Ik; Kim, Sang Wook; Kim, Jie-Hyun; Kim, Hyung Keun; Shin, Jeong Eun; Yoon, Won Jae; Lee, Yong Kang; Chung, Kwang Hyun; Cho, Soo-Jeong; Shin, Hyun Phil; Cho, Sun Young; et al. (Clinical endoscopy, 2020)
The area of endoscopic application has been continuously expanded since its introduction in the last century and the frequency of its use also increased stiffly in the last decades. Because gastrointestinal endoscopy is naturally exposed to diseased internal organs and contact with pathogenic materials, endoscopy mediated infection or disease transmission becomes a major concern in this field. Gastrointestinal endoscopy is not for single use and the proper reprocessing process is a critical factor for safe and reliable endoscopy procedures. What needed in these circumstances is a practical guideline for reprocessing the endoscope and its accessories which is feasible in the real clinical field to guarantee acceptable prevention of pathogen transmission. This guideline contains principles and instructions of the reprocessing procedure according to the step by step. And it newly includes general information and updated knowledge about endoscopy-mediated infection and disinfection. Multiple societies and working groups participated to revise; Korean Association for the Study of the Liver, the Korean Society of Infectious Diseases, Korean College of Helicobacter and Upper Gastrointestinal Research, the Korean Society of Gastroenterology, Korean Society of Gastrointestinal Cancer, Korean Association for the Study of Intestinal Diseases, Korean Pancreatobiliary Association, the Korean Society of Gastrointestinal Endoscopy Nurses and Associates and Korean Society of Gastrointestinal Endoscopy. Through this cooperation, we enhanced communication and established a better concordance. We still need more researches in this field and fill up the unproven area. And our guidelines will be renewed accordingly.